DESIGN AND IMPLEMENT ADAPTIVE NEURAL NETWORK SOFTWARE FOR ROUTING DATA PROCESS IN COMPUTER NETWORK - Dadio Nugroho; Risa Ekowati; Prima Kristalina; Mauridhi Hery P (KH. A. Wahab Hasbullah University, 2008)
The data transmission in computer network is very important. Therefore, this issue always need a serious attention, especially in the middle and wide area networking which consist of many routers. This Adaptive Neural Network's softwareÂ for routing data in computer network (which is called JST Router later) is designed to solve a routing problem for choosing the best data routing path using Backpropagation Algorithm of Neural NetworkKeywords : routing table , routing algorithms, routing protocols , Artificial Neural Networks .